Experimental eva luation of the protective properties of the original chewing compositions in relation to the toxic effect of water soluble nicotos-containing substances of the tobacco on an immature organism - Adamovich, Anna V.; Shevlyakov, Vitalii V.; Yuraha, Tamara M. (Experimental Biology and Biotechnology, 2019)
On the experimental model of subchronic oral alkaloidization of immature white rats with their 59-daily consumption of aqueous extract from tobacco products in cyclically increasing concentrations of the total alkaloids, the potential protective properties of the developed original prophylactic chewable compositions (based on mexidol, glycine, vitamin complex and phytocomponents) in relation to toxic effect of the complex of soluble substances of tobacco were studied. The results of the study testify to the protective effect of prophylactic chewable compositions with their 2-week consumption of alkaloidized animals on models of continuing consumption of aqueous extract from tobacco products and its termination, which was reflected in the normalization or significant improvement of morphofunctional indicators of the organism of intoxication genesis in alkaloidized animals. The developed formulations of prophylactic chewable compositions are promising for drug support in the prevention and cessation of tobacco use by young people and are recommended for further study for this purpose.
Keywords: tobacco consumption by adolescents; water extract from tobacco products; prophylactic chewing compositions; protective effect; immature rats